Hidrojel ve Silikon Hidrojel Yumuşak Kontakt Lenslerin Optiksel Karakterizasyonu - Özmenteş, Reşit; Korkut, Abdulkadir (Fırat University, 2024)
Kontakt lensler, görme kusurlarını düzeltmede gözlük alternatifi olarak ortaya çıkan biyomalzemelerdir. Bu çalışmada, Nesofilcon A (Hidrojel-Hy) ve Delefilcon A (Silikon Hidrojel-SiHy) günlük tek kullanımlık yumuşak kontakt lensler UV-görünür ışık spektroskopisi kullanılarak optiksel olarak incelenmiştir. Lenslerin optik soğurma ve geçirgenlik ölçümleri UV-görünür ışık spektrofotometresi ile alınarak, göze gelen radyasyonun zararlı kısmını bloke etme ve zararsız kısmını geçirme özellikleri incelenmiştir. Soğurma spektrumundan, Nesofilcon A lensinin ultraviyole ışığı daha iyi emdiği görülmüştür. Nesofilcon A ve Delefilcon A lenslerinin optik soğurma katsayısı spektrumlarından soğurma kenarları 386 ve 325 nm, optik bant aralığı değerleri ise sırasıyla 3.34 ve 3.98 eV olarak elde edilmiştir. Ayrıca lenslerin kırılma indisi profilleri çizilmiştir. 550 nm dalga boyunda lenslerin kırılma indeksleri Nesofilcon A ve Delefilcon A için sırasıyla 1.55 ve 1.77 olarak hesaplandı. Delefilcon A lensi görünür ışığı iyi iletirken, Nesofilcon A lensi UV ışığını daha iyi bloke ettiği ve kırılma indeksinin üretici tarafından belirtilen 1.40 değerine daha yakın olduğu belirlendi.

Contact lenses are biomaterials that have emerged as an alternative to glasses in correcting vision defects. In this study, Nesofilcon A (Hydrogel-Hy) and Delefilcon A (Silicone Hydrogel-SiHy) daily disposable soft contact lenses were optically examined using UV-visible light spectroscopy. Optical absorption and transmittance measurements of the lenses were taken with a UV-visible spectrophotometer, and their properties of blocking the harmful part of the radiation to the eye and transmitting the harmless part were investigated. From the absorption spectrum, it was seen that the Nesofilcon A lens absorbed ultraviolet light better. From the optical absorption coefficient spectra of Nesofilcon A and Delefilcon A lenses, the absorption edges were obtained as 386 and 325 nm, and the optical band gap values were 3.34 and 3.98 eV, respectively. Additionally, the refractive index profiles of the lenses were plotted. The refractive indices of the lenses at 550 nm wavelength were calculated as 1.55 and 1.77 for Nesofilcon A and Delefilcon A, respectively. While the Delefilcon A lens transmitted visible light well, the Nesofilcon A lens blocked UV light better and its refractive index was determined to be closer to the 1.40 the value specified by the manufacturer.
Optical Characterization of Hydrogel and Silicone Hydrogel Soft Contact Lenses
Keywords: Nonlinear Optics and Spectroscopy; Doğrusal Olmayan Optik ve Spektroskopi; Biomaterial; Biyomateryaller